An In-Silico and In-Vitro Study of Imatinib and Naringin Combination for Inhibiting P-Glycoprotein and Delaying Drug Resistance in Chronic Myeloid Leukemia (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: The present study describes the potential use of naringin (NAR), a flavanone glycoside, in combinationwith imatinib (IMT), a signal transduction inhibitor used in chronic myeloid leukemia (CML). The study aimed toinvestigate whether NAR could help overcome the multidrug resistance of IMT by inhibiting the overexpressionof the P-glycoprotein gene. Materials and Methods: Molecular docking approach is used to investigate thebinding affinity of IMT and NAR to human P-glycoprotein. The results showed that IMT had stronger interactionswith P-glycoprotein than NAR, indicating better stability with a binding energy of −7.3 kcal/mol comparedto −5.6 kcol/mol for NAR. However, NAR demonstrated an excellent affinity toward human P-glycoprotein.Results: To investigate the effect of NAR and IMT combination on P-glycoprotein expression, flow cytometrytechnique on K562 cell lines is used. The results displayed that IMT alone at a concentration of 1 μM had a P-gpexpression of 73.6%. Nevertheless, P-gp expression was substantially decreased to 9.7% when coupled with NARat higher doses (5–30 µM). Moreover, pure NAR alone also showed suppression of P-gp expression. In summary,the study suggests that the combinatorial approach of IMT with NAR could enhance anticancer activity and delaydrug resistance by reducing P-gp expression in K562 cell lines. Conclusion: These results support the potentialuse of NAR as an adjuvant therapy to IMT in the management of CML. However, further studies are needed toconfirm the efficacy and safety of this approach in clinical settings.